Production of Σ(1385)± and Ξ(1530)0 in proton-proton collisions at √s = 7 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (The European physical journal. C, Particles and fields, 2015)
The production of the strange and double-strange baryon resonances (Σ(1385)±, Ξ(1530)0) has been measured at mid-rapidity (|y| <0.5) in proton–proton collisions at s√ = 7 TeV with the ALICE detector at the LHC. Transverse momentum spectra for inelastic collisions are compared to QCD-inspired models, which in general underpredict the data. A search for the ϕ(1860) pentaquark, decaying in the Ξπ channel, has been carried out but no evidence is seen.